LDMD: A database of microbes in human lung disease - Xu, Li-Qun; Yang, Jing; Liang, Weicheng; Chen, Jiang; Sun, Zepeng; Zhang, Qiang; Liu, Xinlong; Qiao, Feng; Li, Jian (Frontiers in Microbiology, 2023)
Lungs were initially thought to be sterile. With the development of sequencing technologies, various commensal microorganisms, especially bacteria, have been observed in healthy human lungs. Many studies also linked lung microbes to lung diseases caused by infections. However, few databases have concentrated on lung metagenomic data, providing microbial compositions and corresponding metadata information. Such a database would be handy for researching and treating lung diseases. In this study, we established the Lung Disease Microorganisms Database (LDMD), a comprehensive database of lung disease microbes. To provide researchers with a preliminary understanding of lung microbes and their research methods, the LDMD collected nearly ten thousand works of literature in respect of more than 30 diseases, gathered basic information such as the source of lung microbes samples, sequencing methods, and processing software, and analyzed the metagenomic sequencing characteristics of lung microbes. In addition, the LDMD also contained data collected in our laboratory. The LDMD provided sequence analysis capabilities, allowing users to upload their sequencing results, align them with data collected in the database, and obtain the results visually. In conclusion, the LDMD possesses a variety of functionalities that provide a convenient and comprehensive resource for studying lung metagenome and treating lung diseases.